What hinders the women entrepreneurial Culture? An answer from District faisalabad, pakistan - Imtiaz, Aisha; Syed, Nausheen (International Journal of Psychosocial Rehabilitation, 2020)
Micro-finance program extends small loans to very poor people for self-employment projects that generate income, allowing them to care for themselves and for their families. Micro-finance enables an entrepreneur to build a business or expand the existing business and create a better change in their lives. Microfinancing institutions (MFIs) provide opportunity for people who are living under poverty lines by investing the affordable funds/capital and somehow by providing their management expertise. This study shows the effect of micro-financing on small business and the implications for poverty reduction. The respondents were the clients of Akhuwat Foundation, District Faisalabad. Objectives of study are to assessment of income generation by microfinance to problems encountered by women in acquiring and using micro finance, to assess impact of loan borrowed from Akhuwat. Another objective of study is to examine entrepreneurial hinders that a women entrepreneur have to face in Pakistan. Study has been conducted in Faisalabad. 130 respondents have been chosen by systematic random sampling from urban and rural areas. Data is collected through structured questionnaire and personal interviews and linear regression analysis has been used through SPSS 23 to find statistical significance of hypothesis for possible acceptance or rejection. Study showed that entrepreneurial hinder like Finance, Sexual harassment, gender discrimination and education and working experience have an impact on women entrepreneurship.